MENINGKATKAN PERSPEKTIF POSITIF MASYARAKAT TENTANG OBYEK WISATA ALAM AIR TERJUN AEK MARTUA DESA BANGUN PURBA - Makmur., Theresia Irma Cahyani, Hidayat, (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2017)
The purpose of this study was to determine the perspectives of society and of the efforts that can be done to improve the public a positive perspective on the natural attractions waterfall Aek Martua Desa Bangun Purba. This research is a qualitative descriptive study, which this research aims to create a picture of people's perspectives on the natural attractions and effort that can be applied to enhance the positive perspective of the community in the development of the natural attractions waterfall Aek Martua. This research was conducted with several stages, namely 1) the data collection phase, 2) analyzing the data, 3) discussion of results. Then make conclusions. Of the 30 samples (Non-Probability Sampling: Snowball Sampling) is used, as many as 22 people (73%) showed a negative perspective on the development of the natural attractions waterfall Aek Martua and as many as 8 people (27%) gave a positive perspective. Efforts should be made to increase the positive perspective of the community consists of four (4) key indicators, namely 1) Knowledge, 2) Skills, 3) Supervision, and 4) Role of Government.